Stubbtransporter och bränslekvalitet hos stubbved - Lindberg, David (SLU/Dept. of Forest Resource Management, 2008)
Stump wood is a hot alternative when the heating plants demands more and more forest fuel. The aim with the study has bean to calculate the costs in four different systems for transportations of stump wood, examine if there are any differences in fuel quality for the stump wood in the different systems, analyse if the fuel quality in stump wood is affected with the time it lays by the road side and how much space the stump wood demands on the road side. To calculate the costs for the different systems a system analysis was carried out, where some of the costs were collected through field studies on Holmen Skog stump experiment and other costs were collected from literature and contacts. Data for the fuel quality study was collected from Eons heat plant in Norrköping. Data for the study of how much space stump wood takes along a roadside was collected from field studies.